Comparing the physical effects of combining small-sided games with short high-intensity interval training or repeated sprint training in youth soccer players: A parallel-study design - Nobari, H.; Silva, A. F.; Vali, N.; Clemente, F. M. (International Journal of Sports Science & Coaching, 2023)
Most of the research combining small-sided games (SSGs) with high-intensity interval training (HIIT) is using the short or long forms of HIIT. However, other types of HIIT as repeated sprint training (RST) could enhance different stimuli. The purpose of the current research was to analyze the within- and between-group variations of physical fitness and body composition of two combined training interventions: (i) SSGs combined with a short high intensity interval training (sHIIT); and (ii) SSGs combined with a RST. This study followed a randomized parallel study design. Twenty-eight youth soccer players (age: 17.3 ± 0.5) belong to the same team were assigned equally to two intervention groups: SSG + sHIIT versus SSG + RST. Training intervention lasted 4 weeks, with a 2-session/week frequency. The players were tested twice, once before and after the intervention with the following tests: skinfolds (fat mass); Sargent jump test (SJT); standing long jump; sprinting time at 10-, 20-, or 30-m; 5-0-5 for time and deficit; 30-15 intermittent fitness test (30-15IFT) based on the final velocity, and repeated sprint ability (RAST) for peak, minimum, average power, and fatigue index. A mixed analysis of variance was conducted to considering factor × time effect. Between-group analysis revealed no significant differences at baseline and post-intervention period for fat mass, sprinting time at 10-, 20-, and 30-m, change-of-direction (COD) time and deficit, SJT and standing long jump, final velocity at 30-15IFT and RAST peak, average power, and fatigue index (p > 0.05). Within-group analysis revealed that both groups significantly reduced fat mass (p = 0.001), SJT (p = 0.001), standing long jump (p = 0.001), sprint time at 10- and 20-m (p = 0.001), 30-m (p = 0.002), COD time (p = 0.001) and deficit (p < 0.05), RAST average (p < 0.05), and final velocity 30-15IFT (p = 0.001). Only SSG + RST had significant improvements on COD deficit and peak power (p < 0.05). The result of the current research suggests that either SSG + sHIIT or SSG + RST are effective for improving physical fitness in youth soccer players, with a multiple beneficial effect on locomotor profile, speed and COD, jumping performance and repeated sprint ability.